TONGKAT PINTAR UNTUK PENYANDANG TUNANETRA BERBASIS MIKROKONTROLER - Bimantoro, Mohammad Nur; Rasmana, Susijanto Tri; Susanto, Pauladie (Journal of Control and Network Systems (JCONES), 2017)
Visual impairment is a condition where a person has in his vision disturbance, both of which still have some usable vision (low vision) or who already legally blind (Total Blind). To perform daily activities, blind to maximize the function of the other senses such as touch, smell or hearing due to reduced function of the sense of sight. Blind People usually use a cane to help him walk, but with these sticks blind space is limited and not freely due to detect objects around to be with tapping stick around foothold when walking. Therefore in this final project will be made of a stick-based smart mikorokontroler. This wand uses 2 ultrasonic sensor that is placed at the top and bottom of the stick. Sensors on ditujukkan to detect objects relatively high such as doors, pillars, walls, fences, and other high objects. While under ditujukkan sensor to detect uneven surfaces and low as rocks, holes, pavements or other low objects. To provide information to users stick uses sound output as a warning sign to avoid walking nearby objects so that a wider space for the visually impaired and help facilitate them to carry out all its activities.